Pengaruh Daya Tarik Wisata Dan Kualitas Pelayanan Terhadap Minat Kunjung Konsumen Kopi Nako Kebon Jati Bogor - Yudhatama, Muhammad Dendy; Manurung, Tarida Marlin Surya (Jurnal Ilmiah Pariwisata Kesatuan, 2025)
The number of cafes in Bogor City has increased very significantly. The increase in cafes moves along with the rise in tourist visits to Bogor. Many cafes are starting to offer natural beauty and have become one of tourist interest in the city of bogor. Kopi Nako Kebon Jati is a cafe whose natural beauty is widely discussed through F&B cafes on several social media. Kopi Nako Kebonjati is a cafe that introduces the natural beauty of the city of Bogor from a height and natural views and the city of Bogor. This study reach out the knowledge of influence tourist attractions and service quality have give on interest in visiting Kopinako Kebonjati Bogor. Using a primary data that collected by spreading questionnaires to Kopinako Kebonjati visitor as a respondents. The number of respondents determined by using Slovin equation so that there were 118 respondents. The data in this study processed using SPSS statictival software version 26 and used multiple linear regression as a estimation model. The study showed that there is a positive significant effect on interested in visiting caused by tourist attraction, on the other hands there is a similar effect caused by service quality interested in visiting. The test results also found that there was a simultaneous influence exerted by attractiveness and service quality on visiting interest. Key Words: Interested in Visiting Tourist Attraction, Service Quality